NEEDS ANALYSIS OF MECHANICAL ENGINEERING STUDENTS IN LEARNING ENGLISH FOR SPECIFIC PURPOSES - Meiristiani, Noeris; Ekawati, Yulia Nur (Research And Innovation In Language Learning (RILL), 2018)
English subject that is learnt in Mechanical Engineering Study Program is different from English subject learnt in other programs, relating to the aspects of target situation, studentsâ weaknesses, studentsâ wishes and their needs. This research aims to find out Mechanical Engineering studentsâ problems in learning English, studentsâ needs in learning English and the process of designing syllabus of English subject. This research is case study using qualitative approach. The research participants are 40 students of Mechanical Engineering in third semester, in the academic year of 2017/2018 and two English lecturers who teach in Mechanical Engineering Study Program. The instruments to collect the data are questionnaire, interview and documentation (studentsâ achievement). Data moreover are reduced, displayed and then conclusions are drawn. The research results show that English subject is needed in Mechanical Engineering department. Studentsâ needs in learning English related with material aspects of listening, speaking, reading, writing, pronunciation, grammar and vocabulary. In addition, the materials of mechanical engineering and application letter using English are also needed. Moreover, studentsâ problems in learning English are studentsâ lack confidence in mastering English both orally and in written. Studentsâ weaknesses in mastering pronunciation, grammar and vocabulary make English subject difficult to learn. In addition, they do not get used to reading and writing English texts. From the results, it is then recommended to review and design the syllabus of English for Mechanical Engineering which is suitable with studentsâ needs and give benefits for students and institution.